Trimethylamine-N-Oxide Pathway: A Potential Target for the Treatment of MAFLD - Li, Xun; Hong, Jia; Wang, Yao; Pei, Maohua; Wang, Luwen; Gong, Zuojiong (Frontiers in Molecular Biosciences, 2021)
Trimethylamine-N-oxide (TMAO) is a molecular metabolite derived from the gut flora, which has recently emerged as a candidate risk factor for metabolic dysfunction-associated fatty liver disease (MAFLD). TMAO is mainly derived from gut, where the gut microbiota converts TMA precursors into TMA, which is absorbed into the bloodstream through the intestinal mucosa, and then transformed into TMAO by hepatic flavin monooxygenases (FMOs) in the liver. High-nutrient diets rich in TMA precursors, such as red meat, eggs, and fish, are the main sources of TMAO. Excessively consuming such diets not only directly affects energy metabolism in liver, but also increases the concentration of TMAO in plasma, which promotes the development of MAFLD by affecting bile acid metabolism, unfolded protein response, and oxidative stress. In this review, we focused on the relationship between TMAO and MAFLD and summarized intervention strategies for reducing circulating TMAO concentration, aiming at providing new targets for the prevention and treatment of MAFLD.